The effects of iridium nanoparticles in radiation dose enhancement in external beam radiation therapy - Isa, Nur Amanina Md (Universiti Sains Malaysia, 2016)
Metal based nanoparticles such as gold nanoparticles, silver nanoparticles, iron oxide nanoparticles and gadolinium nanoparticles have been investigated for their potential to increase the therapeutic effects of radiotherapy. However, Iridium nanoparticles have never been tested so far and the purpose of this study is to investigate the effects of Iridium nanoparticles on radiation dose enhancement in External Beam Radiation Therapy (EBRT). The HeLa cells were incubated with two different concentrations of Iridium NPs at 0.1 mM/L and 0.5 mM/L. The samples of HeLa cells were then irradiated with photon beam of 6 MV energy and electron beam of 6 MeV energy. Cumulative dose ranges from 0.5 to 10 Gy were applied during irradiation process. The cells’ proliferation after irradiation were observed by mean of clonogenic assay. The evaluation of the radiosensitivity of HeLa cells with and without the inclusion of Iridium nanoparticles towards both type of radiation beams were done by plotting survival curves and was fitted to linear quadratic formalism. The results shows that DEF obtained for photon beam at 0.1 mM/L and 0.5 mM/L are 1.08 and 2.10 respectively while for electron beam the values generated at 0.1 mM/L is 1.17 and for 0.5mM/L is 1.13. The cell survival curves of HeLa cells with inclusion of Iridium nanoparticles was steeper compared to the control cells. This indicated that Iridium nanoparticles shows dose enhancement effect on HeLa cells. It is also established that the shape of the cell survival curve is affected by different radiation beams and Iridium NPs concentration. This study concluded that the Iridium nanoparticles are proven to be one of the potential radiosensitizers in radiotherapy. Dose enhancement effects is observed to be dependent on radiation beam types and nanoparticles